1982
DOI: 10.2355/isijinternational1966.22.925
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of reduction of synthetic chromite with carbon.

Abstract: SynopsisSynthetic Chromite was prepared and reduction studies were carried out with di fferent amounts of carbon in the mixture in the temperature range 1150-'1300 °C. Partially reduced material was analysed by X-ray di , f f'ractometry which indicated the presence of Fe, Cr203, unreduced chromite, Cr304 and residual graphite. An analysis of the results on the basis of quasi steady state equation for diffusion control through product layer, phase boundary reaction and unsteady state diffusion of oxygen, reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Next, the activation energy was evaluated in the temperature range of 1373-1573 K, with a value of 299.27 kJ/mol being obtained for the formation reaction of Mn 7 C 3 in the present work. This value is nearly equal to that of activation energy for the carbide formation reaction of the metal oxide such as Mn oxide and Cr oxide, which are from 217 to 310 kJ/mol [10,11,13,14]. It has been known that the carbide formation reaction by CO and carbon or carbide are controlled by Boudouard's reaction and interfacial chemical reaction or solid state diffusion of carbon, respectively [10][11][12][13][14]20,21].…”
Section: Chang Ho Eom and Dong Joon Minmentioning
confidence: 96%
See 2 more Smart Citations
“…Next, the activation energy was evaluated in the temperature range of 1373-1573 K, with a value of 299.27 kJ/mol being obtained for the formation reaction of Mn 7 C 3 in the present work. This value is nearly equal to that of activation energy for the carbide formation reaction of the metal oxide such as Mn oxide and Cr oxide, which are from 217 to 310 kJ/mol [10,11,13,14]. It has been known that the carbide formation reaction by CO and carbon or carbide are controlled by Boudouard's reaction and interfacial chemical reaction or solid state diffusion of carbon, respectively [10][11][12][13][14]20,21].…”
Section: Chang Ho Eom and Dong Joon Minmentioning
confidence: 96%
“…Furthermore, several studies have reported the rate determining step of the carbothermic reduction of metallic oxide [7,8,[12][13][14][15][16][17][18][19]. In the reduction of a metallic oxide by carbon, it is assumed that the overall rate can be controlled by the gasification of graphite at temperatures up to 1273 K [7,[12][13][14]. At higher temperatures, this reaction proceeds quite rapidly, which may lead to the case of a diffusion-controlled reaction [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Murti et al [10] studied the reduction of synthetic chromite by carbon at 1423 to 1573 K. In this study it was concluded that reduction was controlled by diffusion of oxygen in the chromite. The same authors studied the reduction of chromite ore at 1513 to 1583 K. In this case, the reduction process was found to be controlled by the diffusion of oxygen in the ore to the gas/solid interface.…”
Section: Carbon As Reductantmentioning
confidence: 99%
“…Various possible mechanisms controlling the rate of reaction have been discussed in literature [8][9][10][11].…”
Section: Carbon As Reductantmentioning
confidence: 99%